Tetrandrine, an Activator of Autophagy, Induces Autophagic Cell Death via PKC-α Inhibition and mTOR-Dependent Mechanisms - Wong, Vincent Kam Wai; Zeng, Wu; Chen, Juan; Yao, Xiao Jun; Leung, Elaine Lai Han; Wang, Qian Qian; Chiu, Pauline; Ko, Ben C. B.; Law, Betty Yuen Kwan (Frontiers in Pharmacology, 2017)
Emerging evidence suggests the therapeutic role of autophagic modulators in cancer therapy. This study aims to identify novel traditional Chinese medicinal herbs as potential anti-tumor agents through autophagic induction, which finally lead to autophagy mediated-cell death in apoptosis-resistant cancer cells. Using bioactivity-guided purification, we identified tetrandrine (Tet) from herbal plant, Radix stephania tetrandrae, as an inducer of autophagy. Across a number of cancer cell lines, we found that breast cancer cells treated with tetrandrine show an increase autophagic flux and formation of autophagosomes. In addition, tetandrine induces cell death in a panel of apoptosis-resistant cell lines that are deficient for caspase 3, caspase 7, caspase 3 and 7, or Bax-Bak respectively. We also showed that tetrandrine-induced cell death is independent of necrotic cell death. Mechanistically, tetrandrine induces autophagy that depends on mTOR inactivation. Furthermore, tetrandrine induces autophagy in a calcium/calmodulin-dependent protein kinase kinase-(CaMKK- 5' AMP-activated protein kinase (AMPK) independent manner. Finally, by kinase profiling against 300 WT kinases and computational molecular docking analysis, we showed that tetrandrine is a novel PKC-inhibitor, which lead to autophagic induction through PKC- inactivation. This study provides detailed insights into the novel cytotoxic mechanism of an anti-tumor compound originated from the herbal plant, which may be useful in promoting autophagy mediated- cell death in cancer cells that are resistant to apoptosis.